The Effectiveness of Pop-Up-based Animation Book to Improve Reading Comprehension Skills of Elementary School Students - Liya Atika Anggrasari; Dian Permatasari Kusuma Dayu (Al Ibtida: Jurnal Pendidikan Guru MI, 2022)
AbstractThis study aims to determine the effectiveness of the use of pop-up-based animated books on the reading comprehension ability of elementary school students in the 3T region, namely Sawojajar, Magetan, Indonesia. This study employed a quantitative research approach. The method used in this research was the experimental method, using true experimental design as the research design. The type of research design employed in this study was post-test only control design. Grade 5 elementary school students in the 3T region, Sawojajar, Magetan participated in this study. The data were collected using observation, interviews, and reading comprehension tests. The obtained data were analyzed using a t-test. The effectiveness value of using the pop-up book is 6.13%. The t-test shows that the Tcount is greater than the Ttable (2.6667 > 2.00). Based on the results of data analysis, it can be concluded that learning using Pop Up-based animated book media is more effective in improving reading comprehension skills than learning using conventional media.Keywords: pop-up, animation book, reading comprehension skills.AbstrakPenelitian ini bertujuan untuk mengetahui keefektifan penggunaan buku animasi berbasis pop-up dalam meningkatkan kemampuan pemahaman membaca siswa sekolah dasar (SD) di daerah 3T yaitu Sawojajar, Magetan, Indonesia. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian kuantitatif dengan metode eksperimen. Desain penelitian menggunakan true experimental design dengan jenis penelitian yang digunakan adalah post-test only control design. Sampel dalam penelitian ini adalah siswa kelas 5 SD di kawasan 3T, Sawojajar, Magetan. Teknik pengumpulan data menggunakan observasi, wawancara, dan tes pemahaman bacaan. Data yang diperoleh dianalisis menggunakan uji t. Efektivitas penggunaan pop-up book adalah sebesar 6,13%. Hasil uji t menunjukkan bahwa T-hitung lebih besar dari T-tabel (2,6667 > 2,00). Berdasarkan hasil analisis data, dapat disimpulkan bahwa penggunaan media buku animasi berbasis pop-up lebih efektif dalam meningkatkan keterampilan membaca pemahaman dibandingkan dengan pembelajaran yang menggunakan media konvensional.Kata kunci: pop-up, buku animasi, kemampuan pemahaman membaca.